Crayola : a visual biography of the world's most famous crayon - Solomon, Lisa (Black Dog & Leventhal Publishers, 2021)
"An authorized, illustrated history of Crayola crayons, from the origins of Binney & Smith as the inventor of carbon black and red oxide pigment to colorful profiles of sky blue, sea green, and the other 118 Crayola colors in circulation today"--